Legal Protection of Songwriters whose Works are Used on Social Media without Permission Based on Copyright Law - Laila Alfida (Universitas Muhammadiyah Surakarta, 2024)
Intellectual property rights are exclusive rights in the fields of technology, science or art and literature. Ownership of intellectual property is not a product, but the result of human thought and creativity, which is in the form of ideas or opinions. Copyright infringers can also be civilly sanctioned with damages for infringement. Damage lawsuit in the form of a request to hand over all or part of the income earned by the infringer from the use of the creation. Legal protection of copyright songs and music for infringement on the Internet, although it is clearly stated in the Copyright Act No. 28 Year 2014, the application of this law is still not effective. This is because people still do not know about copyright laws that protect the copyright of songs and music and what actions are prohibited by law. The same applies to song copyrights. Musicians are not required to register their songs with the National Intellectual Property Office just to protect song copyright because copyright does not arise from the fact of registration.